Role of Secretome in Age-related Changes in the Male Reproductive System: An Add-on Review on the Gut-Brain Axis - Gembong Satria Mahardhika; Norina Agatri (WMJ (Warmadewa Medical Journal), 2025)
Humans are unable to prevent the ageing process. The secretome is a group of bioactive molecules released by cells that may exert paracrine effects on adjacent cells. Recent research indicates that the cellular secretome of mesenchymal stem cells (MSCs) may be useful in the management of idiopathic male infertility. This narrative review was derived from journal articles retrieved through various search engines, including PubMed, Google Scholar, and EBSCO, which were used to compile the reference list. Subsequently, relevant information and journals were collected and reviewed by the authors. The secretome can be examined from multiple perspectives. It may be linked to morphological, histological, and physiological changes in the male reproductive system associated with ageing. These processes may be improved by incorporating the secretome as an anti-inflammatory, anti-apoptotic, and anti-aging agent. Normal gut–testis microbial cooperation supports overall health. Food intake or illness can disrupt the gut microbiota, triggering a cascade that affects fertility. Dysbiotic conditions increase inflammatory markers and damage the gut epithelium, allowing bacteria and inflammatory cytokines to enter the circulation. The secretome also plays a role in balancing the microbiome within the gut–brain axis, thereby contributing to the prevention of fertility impairment. The presence of the secretome may serve as a modulatory factor for age-related changes in male reproductive function, particularly fertility components. Further investigation through additional related studies and systematic reviews is needed to enhance understanding of the relationship between these variables.